New Generation of Artificial MicroRNA and Synthetic Trans-Acting Small Interfering RNA Vectors for Efficient Gene Silencing in Arabidopsis. Issue 1 (19th March 2014) - Carbonell, Alberto; Takeda, Atsushi; Fahlgren, Noah; Johnson, Simon C.; Cuperus, Josh T.; Carrington, James C.
Abstract : Artificial microRNAs and synthetic trans-acting small interfering RNAs produced from new, high-efficiency expression vectors induce reliable gene silencing in Arabidopsis . Abstract: Artificial microRNAs (amiRNA s) and synthetic trans-acting small interfering RNAs (syn-tasiRNA s) are used for small RNA-based, specific gene silencing or knockdown in plants. Current methods to generate amiRNA or syn-tasiRNA constructs are not well adapted for cost-effective, large-scale production or for multiplexing to specifically suppress multiple targets. Here, we describe simple, fast, and cost-effective methods with high-throughput capability to generate amiRNA and multiplexed syn-tasiRNA constructs for efficient gene silencing in Arabidopsis ( Arabidopsis thaliana ) and other plant species. amiRNA or syn-tasiRNA inserts resulting from the annealing of two overlapping and partially complementary oligonucleotides are ligated directionally into a zero background Bsa I/ ccd B-based expression vector. Bsa I/ ccd B vectors for amiRNA or syn-tasiRNA cloning and expression contain a modified version of Arabidopsis MIR390a or TAS1c precursors, respectively, in which a fragment of the endogenous sequence was substituted by a ccd B cassette flanked by two Bsa I sites. Several amiRNA and syn-tasiRNA sequences designed to target one or more endogenous genes were validated in transgenic plants that (1) exhibited the expected phenotypes predicted by loss of target gene function, (2) accumulated high levels of accurately processed amiRNA s or syn-tasiRNA s, and (3) had reduced levels of the corresponding target RNAs.